MitoTam-01 Trial: Mitochondrial Targeting as Plausible Approach to Cancer Therapy. Comment on Yap et al. Complex I Inhibitor of Oxidative Phosphorylation in Advanced Solid Tumors and Acute Myeloid Leukemia: Phase I Trials. Nat. Med. 2023, 29, 115-126 - Neuzil, Jiri; Rohlena, Jakub; Werner, Lukas; Bielcikova, Zuzana (Cancers, 2023)
A recent paper published in Nature Medicine reported on the Phase I clinical trial of a mitochondria-targeting anti-cancer agent IACS-01059 in patients with acute myeloid leukemia (AML) and solid tumors [...].